Malignancy and lymphoid proliferation in primary immune deficiencies; hard to define, hard to treat - KOÇ, AHMET; ÖZEN, AHMET OĞUZHAN; TOKUÇ, AYŞE GÜLNUR; AYDINER, ELİF; TÜRKÖZ, HÜSEYİN KEMAL; EKER, NURŞAH; TRUE, ÖMER; BARIŞ, SAFA; BOZKURT, SÜHEYLA (WILEY, 2020)
Background Regarding the difficulties in recognition and management of the malignancies in primary immune deficiencies (PIDs), we aimed to present the types, risk factors, treatment options, and prognosis of the cancers in this specific group. Methods Seventeen patients with PID who developed malignancies or malignant-like diseases were evaluated for demographics, clinical features, treatment, toxicity, and prognosis. Results The median age of malignancy was 12.2 years (range, 2.2-26). Lymphoma was the most frequent malignancy (n = 7), followed by adenocarcinoma (n = 3), squamous cell carcinoma (n = 2), cholangiocarcinoma (n = 1), Wilms tumor (n = 1), and acute myeloid leukemia (n = 1). Nonneoplastic lymphoproliferation mimicking lymphoma was observed in five patients. The total overall survival (OS) was 62.5% +/- 12.1%. The OS for lymphoma was 62.2% +/- 17.1% and found to be inferior to non-PID patients with lymphoma (P = 0.001). Conclusion In patients with PIDs, malignancy may occur and negatively affect the OS. The diagnosis can be challenging in the presence of nonneoplastic lymphoproliferative disease or bone marrow abnormalities. Awareness of susceptibility to malignant transformation and early diagnosis with multidisciplinary approach can save the patients' lives.
Keywords: cancer; lymphoid proliferation; lymphoma; malignancy; primary immune deficiency; prognosis; IMMUNODEFICIENCY SYNDROMES; IMMUNOLOGICAL PHENOTYPE; CANCER; CHILDREN; SECONDARY; MUTATION; PATHWAY; PATIENT; PIK3R1